Structural transformation of MnTiO3 with manganese dioxide and titanium dioxide influenced by solid-state calcination kinetics - Ritushree Shaily; Abhishek Prasad; Kuldeep Kumar; Dilip Kumar Meena (Next Materials)
In the present study, MnTiO3 was prepared using the conventional solid-state reaction method and then calcined at 1200℃ for various times: 6 h, 12 h, 18 h, and 24 h. The XRD results confirm that the formation of MnTiO3, calcined at 1200℃ for 24 h, exhibits successful crystallization and stabilization in a hexagonal structure with space group R-3h. The average crystallite size, calculated using the Scherrer equation, is 47.16 nm, and through the modified Scherrer equation is 54.82 nm. However, the evaluated crystallite size was obtained by the Uniform Deformation Method (UDM), and the Uniform Stress Deformation Model (USDM) was 71.1 nm, respectively. The crystallite size value is 72.21 nm, as calculated by the Uniform Deformation Energy Density Model (UDEDM). Furthermore, the Size-Strain Plot method yields a crystallite size of 40.54 nm. The strain value, 7.15×10−3 and 4.132×10−3 has been obtained through the Uniform Deformation Model, and the Size-Strain Plot, respectively. The stress and energy density, i.e., 0.128 GPa and 2.94 MJm−3, respectively, were obtained by the Uniform Deformation Energy Density Model. The surface morphology of the 24-hour calcinated MnTiO3 sample shows that the average particle size is 7.05μm, as obtained by Scanning Electron Microscope.